The Effect of Audit Committee Characteristics and Profitability on Timeliness of Financial Report Submission (Case Study of Companies Listed in the Jakarta Islamic Index 2016-2020 Period) - Siti Ika Nuraini; Budi Utomo (UIN Salatiga, 2021)
The purpose of this study is to analyze the effect of the characteristics of the audit committee and profitability of the timeliness of submission of financial statements, where the audit committee characteristics variable consists of the size of the audit committee, the composition of the independent audit committee, the frequency of the audit committee meeting and the audit committee competency. The object of this research company registered in Jakarta Islamic Index Period 2016-2020 with sampling using the purposive sampling method and obtained a sample of 11 companies. Data testing is done by logistical regression analysis using SPSS 25 tools While the frequency of audit committee meetings and profitability has a negative effect on no significant on the timeliness of the delivery of financial statements.Keywords: Characteristics of the Audit Committee, Profitability, and Timeliness of Financial Report Submission.